Reconciling trademark valuation method for commercial purposes with infringement cases - Noordin, Norrezan (2014)
It is important to specifically conduct research on reconciling trade mark valuation method for commercial purposes with infringement cases due to lack of research in this area. An infringement could cause substantial damage to a company’s trade mark reputation. Not only would it undermine the trade mark’s distinctiveness, it would also hinder the trade mark’s function as a guarantee of the company’s products or services. Due to trade marks’ significant value and increased frequency of infringement, effective measures are required to discourage infringement and to assess damages. One crucial measure for enforcing trade mark damages assessment is to choose the correct method. A hypothesis for this study is trade mark valuation method used by market is different from the method in infringement cases. This study proposes appropriate trade mark damages assessment guideline that courts should adopt in assessing damages. This study employs qualitative research methods where secondary data on the methods of valuation are analyzed as trade mark valuation is an exercise to estimate the trade mark value including its damages assessment for infringement. Data in the form of trade mark infringements cases from courts in Malaysia, the UK, the USA and Australia are also analyzed and grouped to find the means to assess damages in trade mark infringement. This study finds that there is no consistent method to value trade mark due to the distinctive characteristics, different markets and other factors each industry possesses.Existing practice of assessing damages in court is also not convincing because there is no clear format of assessment. In addition, although there are limitations in the three main valuation methods namely the cost approach, market approach and income approach, the latter is found to be more appropriate as the basis of the proposed guideline to assessing damages in trade mark infringements. The proposed guideline assists in identifying the type of evidence and the appropriate approach to assess the damages in trade mark infringements.